(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2010)
The action of 2-cyano-3,4,4-trimethyl-2-butene-4-olid (UCL) on cumene autooxidation kinetics in chlorobenzene solution initiated by AIBN at 353 K has been studied. It has been established that UCL practically does no act on the steady state reaction rate, but in its presence some induction period is being noticed which depends on [UCL]0. Ionol as well TEMPO act as classical inhibitors, but their inhibitory action is being decreased in UCL presence. An interaction antagonism is being noticed in presence of UCL+ionol and UCL+TEMPO pairs. Probably it is due to interaction of UCL molecule with ionol as well with TEMPO. It is assumed that UCL may be cooxidized with cumene.